2021
DOI: 10.1093/eurpub/ckab078
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes among women of migrant origin in Finland—a population-based study

Abstract: Background Migrant women may have a higher risk for gestational diabetes mellitus (GDM) and the related adverse outcomes. We studied the prevalence of GDM among migrant-origin women in Finland. Methods This study used data from the nationwide Medical Birth Register. Information on the most recent singleton births of women delivering between 2004 and 2014 (N = 379 634) was included. Women were classified into nine regional cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
3
0
2
Order By: Relevance
“…However, the healthy migrant effect may not explain the lower risk of HDP among women of migrant origin because some of these migrant origin groups also have an increased risk of several other adverse pregnancy outcomes such as gestational diabetes mellitus, emergency cesarean delivery, pre‐term birth and low birthweight. 21 , 22 It is likely that a variety of genetic and lifestyle factors play a significant role for HDP. A previous study examining the metabolic syndrome among migrants in Finland found that while many metabolic risk factors were present, average blood pressure levels and the prevalence of hypertension was lower among women of Somali and Kurdish origin compared with women in the general Finnish population.…”
Section: Discussionmentioning
confidence: 99%
“…However, the healthy migrant effect may not explain the lower risk of HDP among women of migrant origin because some of these migrant origin groups also have an increased risk of several other adverse pregnancy outcomes such as gestational diabetes mellitus, emergency cesarean delivery, pre‐term birth and low birthweight. 21 , 22 It is likely that a variety of genetic and lifestyle factors play a significant role for HDP. A previous study examining the metabolic syndrome among migrants in Finland found that while many metabolic risk factors were present, average blood pressure levels and the prevalence of hypertension was lower among women of Somali and Kurdish origin compared with women in the general Finnish population.…”
Section: Discussionmentioning
confidence: 99%
“…Studien viser at kvinner med innvandringsbakgrunn fra ere land i Sør-Asia, Øst-Asia, Midtøsten og Nord-Afrika samt Russland / tidligere Sovjetunionen hadde høyere risiko for svangerskapsdiabetes enn kvinner fra Finland i justerte analyser (16).…”
Section: Registerstudien Viste Stor Variasjon I Forekomsten Av Svange...unclassified
“…Å forebygge svangerskapskomplikasjoner hos risikogrupper er svaert viktig i oppfølgingen av gravide. At det er høyere forekomst av svangerskapsdiabetes blant innvandrerkvinner (13,15,16), tilsier at det er et stort behov for en forsterket og mer tilpasset oppfølging av innvandrerkvinner i svangerskapet.…”
Section: Noen Forskningsstudier Mangler Relevant Informasjonunclassified
“…It is known that the GDM prevalence markedly differs between different ethnic populations and hence, the region of origin has been recognized as a non-negligible risk factor. However, detailed data about each area and its specific role and importance are sparse and sometimes conflicting (4)(5)(6)(7)(8)(9). Although Asian populations and women from the Sub-Saharan region have long been recognized as being at high risk of developing the disease, women from other regions are also often affected (3,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Migration has been steadily rising and the countries of origin have greatly diversified over the past years. As a consequence, women with migration background were reported to constitute up to 8-14% of the collective of pregnant women in two Nordic countries (8,13). In this context, pregnant women with migration background (especially those from other continents) present specific challenges related to detection and care of GDM that need to be addressed (14).…”
Section: Introductionmentioning
confidence: 99%